Peran Dukungan Orang Tua Terhadap Motivasi Belajar dan Dampaknya pada Hasil Belajar Matematika SMP kelas VII - ali, Muh. Syaifullah S; Yusuf, St. Mutmainnah; Rukman, Nia Kurniaty (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2024)
The objective of this study was to examine role of parental support and mathematics learning outcomes for VII graders. This is a correlation study using a quantitative approach to investigate the relationship between two variables, independent and the dependent variable. The subjects of this study were VII graders of SMP Negeri Ternate, which consist of 30 respondents. A measurement scale will be used as the instrument in this study. The quantitative data analysis was used to analyse the data. According to results: (1) the Sig value of parental support is 0.250. Because the value of Sig. 0.250 is higher than 0.05, it can be concluded that parents’ support has an effect on learning outcomes. (2) as the Sig value is 0.040, the Sig value of learning motivation is 0.040. 0.05, it is possible to conclude that there is no relationship between learning motivation and learning outcomes. (3) Considering the Sig value is 0.04 0.05 and the computed f value is 4.975 > 3.34, it may be assumed that variables (X1) and (X2) have an effect on (Y) based on the decision making on the F test.